KEBIASAAN BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN MASYARAKAT FKIP DI UNIVERSITAS RIAU - Aisyah Dwi Sabtamy; Said Suhil Achmad; Wilson Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Learning habits are a person's way of learning that is done repeatedly so that it becomes a habit to gain knowledge and increase achievement, everyone has their own learning method which in this way can make them study well to increase achievement. This means that with good study habits, the understanding obtained will be more meaningful and the purpose of learning will be achieved, namely obtaining learning achievements in accordance with expectations. The purpose of this study was to determine the study habits of students of the Community education study program at the University of Riau. This research is classified as a descriptive study using a one-variable quantitative approach. The population in this study were all students of the Public Education Study Program at the University of Riau, totaling 226 people from the 2016 2019 class. The sample technique used in this study was Proportionate Stratified Random Sampling, which was used when the population had members / elements that were not homogeneous and proportionally stratified. The instrument in this study was a questionnaire or questionnaire containing 35 statements about learning habits consisting of three indicators. Based on statistical analysis, students' study habits were found to be very high with a percentage of 91.2% and the rest were influenced by other indicators besides the indicators in this study.Key Word: Study Habits